2020
DOI: 10.1002/bio.3812
|View full text |Cite
|
Sign up to set email alerts
|

Spectrofluorometric determination of alogliptin an antidiabetic drug in pure and tablet form using fluorescamine, a fluorogenic agent: application to content uniformity test

Abstract: Alogliptin is an antidiabetic drug that belongs to a group called dipeptidyl peptidase-4 enzyme inhibitors. As the drug contains a primary amino group in its structure, it readily reacts with fluorescamine in slightly alkaline medium (borate buffer, pH 8.8) to form a highly fluorescent product. Emission of this product was measured at 477 nm (λ ex = 387 nm). The linear range between the fluorescence intensity and the drug concentration was 0.1-0.5 μg ml −1 with a good correlation coefficient (0.9986). Limits o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…T A B L E 7 Proposed spectrofluorimetric method application to determine ALO in spiked human plasma UV/Vis spectrophotometry 1-25 [25] UV/Vis spectrophotometry 5-30 [34] HPLC 0.05-1 [30] Spectrofluorometry 0.1-0.5 [38] UV-vis spectrophotometry and (RP-HPLC) 5-35 and 20-100 [7]…”
Section: Application To Biological Fluids (Pharmacokinetic Applicatio...mentioning
confidence: 99%
See 3 more Smart Citations
“…T A B L E 7 Proposed spectrofluorimetric method application to determine ALO in spiked human plasma UV/Vis spectrophotometry 1-25 [25] UV/Vis spectrophotometry 5-30 [34] HPLC 0.05-1 [30] Spectrofluorometry 0.1-0.5 [38] UV-vis spectrophotometry and (RP-HPLC) 5-35 and 20-100 [7]…”
Section: Application To Biological Fluids (Pharmacokinetic Applicatio...mentioning
confidence: 99%
“…[ 1–3 ] ALO’s scientific name is 2‐[[6‐[(3R)‐3‐aminopiperidin‐1‐yl]‐3‐methyl‐2,4‐dioxopyrimidin‐1‐yl][2]methyl]benzonitrile (Figure 1) with empirical formula C 18 H 21 N 5 O 2. [ 4 ] Some attempts have been made to estimate ALO either alone or in conjunction with other medications, including using capillary electrophoresis, [ 5 ] conductometry, [ 6 ] high performance liquid chromatography (HPLC), [ 7–30 ] spectrophotometry, [ 7,17,31–36 ] spectrofluorometry, [ 37,38 ] and thin‐layer chromatography [ 27,39–41 ] methods. The use of costly reagents (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ALG has been determined spectrophotometric, 9–11 spectrofluorometric, 12,13 chromatographic, 14–20 and HPTLC. 21 While the literature review revealed no electrochemical method.…”
Section: Introductionmentioning
confidence: 99%